Electromagnetic navigation bronchoscopy. (January 2011) - Bechara, Rabih; Parks, Christopher; Ernst, Armin
In 2009, lung cancer was estimated to be the second most common form of cancer diagnosed in men, after prostate, and the second, after breast cancer, in women. It is estimated that it caused 159, 390 deaths more than breast, colon and prostate cancers combined. While age-adjusted death rates for this cancer have been declining since 2000, they remain high.